Current Priorities in Health Research Funding and Lack of Impact on the Number of Child Deaths per Year - Leroy, Jef L. (American Public Health Association, 2007)
We determined the proportion of research on childhood mortality directed toward better medical technology (i.e., by improving old technology or creating new technology) compared with research on technology delivery and utilization. We also estimated mortality reductions from a research-funding strategy focusing primarily on developing technology compared with one that also focused on delivery and utilization. Ninety-seven percent of grants were for developing new technologies, which could reduce child mortality by 22%. This reduction is one third of what could be achieved if existing technologies were fully utilized. There is a serious discrepancy between current research and the research needed to save children’s lives. In addition to increased research on the efficacy of treatment, there is an even greater need for increased research on delivery and use of technology.